Environmental citizenship and solid waste management in Chattogram, Bangladesh - Sarmistha Biswas; Ananya Nandy; Nafisa Islam; Nazifa Rafa (Open Economics, 2020)
Chattogram city is grappling with problems caused by inadequate solid waste management (SWM). Because the successful policy intervention regarding proper SWM depends on the intrinsic motivation of the city dwellers along with government intervention, the objective of this paper was to conduct an attitudinal study of the residents of Chattogram regarding their roles and responsibilities towards the SWM, and thus, the sustainable development of the city. It is a cross-sectional study based on a sample size of 150. Data was collected using a structured, pretested questionnaire. The result showed that the residents were unable to prioritize the city's environmental problem over other problems due to the lack of knowledge and awareness about the environmental problems and its impacts on the Chattogram. However, in respect of SWM in the city, their eagerness for participation is appreciable, even though they are more dependent on government policy initiatives. An attitudinal gap was also observed here among the respondents pertaining to the vacuum of knowledge and awareness. Therefore, strong policy decisions and the awareness campaign can make people aware of their roles and responsibilities for a sustainable city and intrinsically motivate them to participate in SWM.
Keywords: 330; behavior; environmental citizenship; solid waste management; sustainable development; sustainable city